A new species of gecko (Squamata: Diplodactylidae: Strophurus) from north Queensland, Australia - Vanderduys, Eric (Zootaxa, 2016)
A new species of diplodactylid gecko in the genus Strophurus Fitzinger, from north Queensland, Australia, is described herein as Strophurus congoo sp. nov. It is a small, pale grey to tan, unpatterned or faintly striped gecko, resembling the phasmid geckos in appearance, habitat and behaviour. However, within Strophurus it is not closely related to the phasmid geckos. It is distinguished from all other Strophurus by a combination of even scalation, dull colouration, small size and short tail length. It is only known to occur in a restricted area of the northern Great Dividing Range, within the Einasleigh Uplands bioregion, in a relatively infertile area of rolling, largely granitic hills, and is only known from spinifex (Triodia) hummock grasslands in open woodland.